2015
DOI: 10.5941/myco.2015.43.4.402
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Two New Talaromyces Species from Crop Field Soil in Korea

Abstract: Two new fungal species of the genus Talaromyces, Talaromyces purpurogenus and Talaromyces trachyspermus from the Trichocomaceae family, were recovered during an investigation of fungal communities in soil collected from the Gangwon-do and Jeollanam-do provinces of Korea. These two species have not been previously officially reported from Korea. In this study, detailed descriptions of internal transcribed spacer rDNA and beta-tubulin gene regions of these two fungi are presented. Morphological features of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…All six acidophilic fungi were clustered in the branch of the genus Talaromyces. We summarized all the references on isolation and identification of Talaromyces since 2015 and found that no acidic culture conditions were involved in the isolation and culture process (including 34 new species of Talaromyces) (Adhikari et al, 2015;Visagie et al, 2015;Chen et al, 2016;Luo et al, 2016;Yilmaz et al, 2016a,b;Barbosa et al, 2018;Jiang et al, 2018;Rajeshkumar et al, 2019). However, in our experiments, all six acidophilic fungi isolates belonged to the genus Talaromyces.…”
Section: Isolation and Phylogenetic Diversity Of Aciduric Fungi Associated With Thai Mangrove Sedimentmentioning
confidence: 54%
“…All six acidophilic fungi were clustered in the branch of the genus Talaromyces. We summarized all the references on isolation and identification of Talaromyces since 2015 and found that no acidic culture conditions were involved in the isolation and culture process (including 34 new species of Talaromyces) (Adhikari et al, 2015;Visagie et al, 2015;Chen et al, 2016;Luo et al, 2016;Yilmaz et al, 2016a,b;Barbosa et al, 2018;Jiang et al, 2018;Rajeshkumar et al, 2019). However, in our experiments, all six acidophilic fungi isolates belonged to the genus Talaromyces.…”
Section: Isolation and Phylogenetic Diversity Of Aciduric Fungi Associated With Thai Mangrove Sedimentmentioning
confidence: 54%
“…Of the lineages selected, it is known that A. parasiticus is a toxigenic fungus with the potential for aflatoxin production, but it must be remembered that mycotoxin production is influenced by complex interactions between abiotic and biotic factors (water activity, temperature, pH, moisture, and storage time) (Copetti et al 2011a;Garcia et al 2011). Researchers have evaluated the occurrence and distribution of aflatoxigenic species as well as the production of aflatoxins during cocoa processing in Bahia (BR), and verified that, despite the high occurrence of aflatoxigenic fungi (A. flavus and A. parasiticus), the levels of aflatoxins found in the samples are low, mainly in the fermentation stage, suggesting that compounds with antitoxigenic properties may be present in cocoa (Adhikari et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the genus Talaromyces has been frequently isolated from soil and root aquatic in Korea [ 50 51 ]. Figs trees are rarely found in Korea.…”
Section: Discussionmentioning
confidence: 99%